Determination of moving objects in space interferometric method - Пепа, Ю.В.; Затикян, Т.О. (Proceedings of National Aviation University (archive), 2007)
Interferometric method for position finding of moving objects, which use satellite radio navigation system for determination self coordinates by use of GPS-technologies, was observed.